Impact of spacing and number of elements on array factor - Siti Fazlina, Maharimi; Mohd. Fareq, Abd. Malek, Dr.; Mohd Faizal, Jamlos, Dr.; Neoh, Siew Chin, Dr; Muzammil, Jusoh (The Electromagnetics Academy, 2013)
Link to publisher's homepage at http://emacademy.org/